Privacy protection for transactions of digital goods - BAO, Feng (Institutional Knowledge at Singapore Management University, 2001)
In this paper we study the problem of how to protect users’ privacy in web transactions of digital goods. In particular, we introduce a system which allows a user to disclose his/her identity information (such as user account or credit card number) to a web site in exchange for a digital item, but prevents the web site from learning which specific item the user intends to obtain. The problem concerned here is orthogonal to the problem of anonymous transactions [RSG98], [RR98] but commensurate with the general problem of PIR (private information retrieval) [CGK95]